The (dis)advantages of clearinghouses before the Fed - Jaremski, Matthew (Journal of Financial Economics, 2018)
Operating in individual cities, US clearinghouses were the closest thing to a central bank before 1914, but they only assisted banks that chose to join the association. Using an annual bank-level database for seven states between 1880 and 1910, this paper shows that after the entry of a clearinghouse member banks were less likely and nonmember banks in the same city were more likely to close. The results are driven by the fact that the presence of clearinghouses led all banks to become more exposed to systemic liquidity risk, yet provided liquidity only to member banks during panics.